Inflammation and autoimmunity in pulmonary hypertension: is there a role for endothelial adhesion molecules? (2017 Grover Conference Series). (March 2018) - Kuebler, Wolfgang M.; Bonnet, Sébastien; Tabuchi, Arata
While pulmonary hypertension (PH) has traditionally not been considered as a disease that is directly linked to or, potentially, even caused by inflammation, a rapidly growing body of evidence has demonstrated the accumulation of a variety of inflammatory and immune cells in PH lungs, in and around the wall of remodeled pulmonary resistance vessels and in the vicinity of plexiform lesions, respectively. Concomitantly, abundant production and release of various inflammatory mediators has been documented in both PH patients and experimental models of PH. While these findings unequivocally demonstrate an inflammatory component in PH, they have fueled an intense and presently ongoing debate as to the nature of this inflammatory aspect: is it a mere bystander of or response to the actual disease process, or is it a pathomechanistic contributor or potentially even a trigger of endothelial injury, smooth muscle hypertrophy and hyperplasia, and the resulting lung vascular remodeling? In this review, we will discuss the present evidence for an inflammatory component in PH disease with a specific focus on the potential role of the endothelium in this scenario and highlight future avenues of experimental investigation which may lead to novel therapeutic interventions.